ChemInform Abstract: A Highly Stable Zeotype Mesoporous Zirconium Metal—Organic Framework with Ultralarge Pores. Issue 13 (March 2015) - Feng, Dawei; Wang, Kecheng; Su, Jie; Liu, Tian‐Fu; Park, Jihye; Wei, Zhangwen; Bosch, Mathieu; Yakovenko, Andrey; Zou, Xiaodong; Zhou, Hong‐Cai
Abstract A zeotype mesoporous zirconium metal‐organic framework, [Zr6(O)4(OH)10(H2O)6 (TATB)2] (TATB: 4, 4′, 4′′‐s‐triazine‐2, 4, 6‐triyl‐tribenzoate) is solvothermally prepared from a mixture of ZrOCl2, TATB, and TFA in N, N‐diethylformamide (autoclave, 120 °C, 12 h).